PERCEPTIONS OF UNIVERSITY STUDENTS REGARDING THE EFFECTS OF ENVIRONMENTAL ISSUES ON HEALTH - budak, sümeyye nur (Turkey Health Literacy Journal, 2024)
Purpose: In this study, the aim is to better understand university students' perceptions of the potential impacts of environmental issues on health and to examine how this may influence future environmental policies and individual behavioral patterns.Method: The research is a descriptive type of survey study. The study included 232 university students. The data were analyzed using, SPSS 23 software. Significance level of p
Keywords: Environmental issues, health, environmental health, environmental health literacy, student